Analysis of Germany's Political Economy During Adolf Hitler's Presidency - Annisa Salsabilla; Aminatuz Zuhriyah (ADALAH, 2021)
German rule under Adolf Hitler lasted from 1930 to 1944. The prime minister embraced fascism. Fascism is a chisel of extreme nationalism that wants authoritarian rule. Fascism encompasses the theories as well as practices on the political, social, and economic systems of fascist parties in Germany. In a fascist system, everyone must submit to the State, the party-centered government, industry, trade, and companies remain under private but are closely monitored by the government, speech habits, the press, etc. are severely restricted. The study aims to find out Adolf Hitler's political strategy to boost Germany's post-world war 1 economy. The research methods used are historical approach. These historical research steps include: heuristic, criticism, interpretation, and historiography. While the data collection technique used in this study is a literature study. The first policy taken by Adolf Hitler's government in leading Germany was to expand its expansion to attack Poland and the Balkan countries, and the other policy was to join the Axis alliance group and engage in World War II against the U.S.-led allied group.